Early Changes in Observed Eating Behaviours and Suboptimal Weight Loss in Gastric Bypass Patients: Preliminary Findings - Heather Spence; Alexander Miras; Julie Sittlington; Carel Le Roux; Alan Spector; Maeve A. Kerr; Chris I. R. Gill; Zsolt Bodnar; David Daniel Kerrigan; Dimitri J. Pournaras; M. Barbara E. Livingstone; Ruth K. Price (Proceedings)
Bariatric surgery is the most effective long-term treatment for severe obesity [...]